2022
DOI: 10.1080/21505594.2022.2147735
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of extraintestinal and diarrheagenic Escherichia coli blood isolates

Abstract: Pathogenic E. coli strains can be classified into two major groups, based on the presence of specific virulence factors: extraintestinal pathogenic E. coli (ExPEC) and diarrheagenic E. coli (DEC). Several case reports describe that DEC can cause bloodstream infections in some rare cases. This mainly concerns a few specific sequence types that express virulence factors from both ExPEC and DEC. In this study, we retrospectively analysed 234 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…MLST is a nucleic acid sequencing-based genotyping method that has been widely used in the study of E. coli and the identification of ExPEC-related clonal complexes or lineages. Different ST types have different drug resistance and virulence characteristics ( Vanstokstraeten et al., 2022 ). Manges et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLST is a nucleic acid sequencing-based genotyping method that has been widely used in the study of E. coli and the identification of ExPEC-related clonal complexes or lineages. Different ST types have different drug resistance and virulence characteristics ( Vanstokstraeten et al., 2022 ). Manges et al.…”
Section: Discussionmentioning
confidence: 99%
“…MLST is a nucleic acid sequencing-based genotyping method that has been widely used in the study of E. coli and the identification of ExPECrelated clonal complexes or lineages. Different ST types have different drug resistance and virulence characteristics (Vanstokstraeten et al, 2022). Manges et al (2019) using metaanalysis described the type, evolution, distribution and characteristics of ExPEC, which showed that ST131 had the highest proportion, and other major lineages included ST69, ST95, ST10, ST405, ST73, ST410, and ST1193.…”
Section: Discussionmentioning
confidence: 99%
“…All of them carried the mdf A gene encoding for the non-specific MdfA multi-drug efflux pump [41]. This gene seems to be commonly present among E. coli isolates independent of the source of isolation [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The raw data were downloaded on BioNumerics v7.6.2 as previously described [ 22, 23 ]. They were trimmed (by exclusion of reads shorter than 35 bp and longer than 251 bp) and assembled de novo with a SPAdes algorithm [ 3, 24 ].…”
Section: Methodsmentioning
confidence: 99%